1999 Turfgrass Research - Kansas State University. Agricultural Experiment Station and Cooperative Extension Service (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
It might be a simple question, such as “Which tall fescue cultivars are best suited for use on lawns?” or possibly a more complicated one, such as “What causes the quality of my bentgrass greens to decline in July?” Answers to these questions and many others are contained in this 1999 edition of Turfgrass Research.
Keywords: Turfgrass; Pest management; Environmental stress; Buffalograss; Bluegrass; Tall Fescue; Bermudagrass; Zoysiagrass